Green box basket / Boniface Benai Anak Siba and Norlina Mohamed Noor - Siba, Boniface Benai; Mohamed Noor, Norlina (2020)
Our world today is facing a severe problem when it comes to pollution. Technology not just contribute to a better way of doing or performing our task, but it also contributes to disaster if no serious action is not taken to overcome the pollution created by technology. Every day we can read or hear about pollution happen all around the world. Still, not many actions are taken to overcome these issues except by a specific group of people or association who is concerned about the future of this world. The effort needs to be started from a lower level, such as the community. Awareness of the day to day activities which can contribute to pollution need to be alert. Society needs to change the way they deal with daily activities by paying more attention to how to reduce pollution. One way to do this is to use a usable box as their basket when doing their shopping. The objective of this invention is to produce an eco-friendly product which can help to reduce pollution. An innovation called Green Box Basket is made from a used box which is safer, environmental and nature friendly compared to the plastic bags which are provided by most of the shops. Plastic bags can be very harmful when they have not correctly disposed of. Any unusable regular paper box is used to invent this green box basket. The green box basket comes from several sizes, depending on the purpose of the users. It is comfortable to hold and can be carried anywhere. The green color is used to make it more attractive and to support the campaign for GO GREEN. The color also represents the intention of the inventor to help keep the environment free from pollution. Compare to other paper bags; Green Box Basket is also multipurpose where the users can also use as storage in their car or at home. With the existence of the green box basket, it is hoped that the pollution caused by plastic bags can be reduced.